2012
DOI: 10.1093/geronb/gbs037
|View full text |Cite
|
Sign up to set email alerts
|

"Feeling Younger, Being Stronger": An Experimental Study of Subjective Age and Physical Functioning Among Older Adults

Abstract: This study is among the first to induce a younger subjective age. It supports the notion that redirecting older adults' attention to downward social comparison with same-aged peers is a promising strategy to maintain a sense of feeling younger. In addition, our results provide an initial positive answer to the question of whether feeling younger translates into better physical functioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
163
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(175 citation statements)
references
References 28 publications
9
163
1
2
Order By: Relevance
“…Although explicitly making people feel favorable compared to younger people in experimental studies has shown short-term improvements in physical [62] and cognitive [61] tasks, respectively, longer-term effects of explicit positive stereotypes in the daily lives of older adults (such as media messages depicting "healthy, active, and happy" older people) and the effects of dominant "successful aging" discourses (found in academic literature and popular press) are less well known. Making upward, rather than downward, social comparisons has multiple likely effects on the health behaviors of older individuals [63].…”
Section: Explicit Priming Of Positive Stereotypes Of Aging (And Sterementioning
confidence: 99%
“…Although explicitly making people feel favorable compared to younger people in experimental studies has shown short-term improvements in physical [62] and cognitive [61] tasks, respectively, longer-term effects of explicit positive stereotypes in the daily lives of older adults (such as media messages depicting "healthy, active, and happy" older people) and the effects of dominant "successful aging" discourses (found in academic literature and popular press) are less well known. Making upward, rather than downward, social comparisons has multiple likely effects on the health behaviors of older individuals [63].…”
Section: Explicit Priming Of Positive Stereotypes Of Aging (And Sterementioning
confidence: 99%
“…the age people perceive themselves to be (Barak & Stern, 1986;Kleinspehn-Ammerlahn et al, 2008). Stephan, Chalabaev, Kotter-Grühn, and Jaconelli (2013) showed that subjective age can be manipulated via downward social comparison. This would complement the suggested internal self-evaluation with an external, comparative evaluation.…”
Section: Predictors For Health Behaviormentioning
confidence: 99%
“…Such an approach can be especially helpful for so-called tailored interventions, which are personalized by a variety of factors to increase intervention participants' commitment and adherence due to a higher personal relevance of the provided content (Hawkins, Kreuter, Resnicow, Fishbein, & Dijkstra, 2008). Social comparison could be one approach to doing so by inducing younger subjective age identities via tailored messages or providing appropriate reference groups for comparison to intervene on subjective physical age (Stephan et al, 2013).…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…For example, two studies have shown that positive feedback can not only improve perceptions of age, but also physical performance (Stephan et al, 2013) and cognitive functioning (Miche and Wahl, 2013).…”
Section: Improving Attitudes Toward Own Agingmentioning
confidence: 99%